Alterações metabólicas em pacientes infectados pelo HIV e HCV - Cezimbra, Helen Minussi (2013)
On June 5, 1981, the CDC (Centers for Disease Control) first published a report of what would be known later as Acquired Immune Deficiency Syndrome (AIDS). More than 30 years after, universally fatal disease was carried to the level of chronic disease, but despite numerous advances, HIV patients have shown increased risk of non-AIDSdefining events and incomplete immune restoration, despite effective virological control, these include morphological, metabolic and atherosclerotic changes. In this context, co-infection with hepatitis C virus (HCV) has attracted interest due to the cumulative and synergistic mitochondrial insults caused by coinfection and enhanced by the use of antiretrovirals. The aim of this study was to determine the prevalence of dyslipidemia and metabolic syndrome in patients infected with the HIV and HCV vírus, with mono or coinfection with each virus. It is a cross-sectional study which included 127 patients, aged 21 to 72 years, 59 with HIV, 36 coinfected and 32 with HCV, males accounted for 48% (62) and 52% female (67). There was a predominance of men among coinfected patients (64% - 23 men and 13 women) and women in the HIV group (66% - 22 men and 37 women). The mean age was 40.6 years (38.5 years HIV, 39.6 coinfected and 45.9 HCV). The white race occurred in 60% of the sample predominantly in all groups. There was no difference between groups in median time to diagnosis of HIV and HCV. To HIV group there were 27% metabolic syndrome by IDF criteria and 26% by HOMA2-IR índex (1,4 cut-off), 63% larger waist by IDF criteria and 26% abdominal obesity. To HIV/HCV coinfection group there were 30% metabolic syndrome by IDF, but 54% by HOMA2-IR index, 42% larger waist, but 52% abdominal obesity. To HCV group there were 25% metabolic syndrome by IDF and 38% by HOMA2-IR index, 67% larger waist and 47% abdominal obesity. The presence of hepatitis C coinfection is responsible for alarming levels of insulin resistance, associated with a more favorable lipid profile that could act as a confounder in the clinical diagnosis of metabolic syndrome.